PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN KONSUMEN SMARTPHONE SAMSUNG DI SEMARANG - Gultom, Melky; Ngatno, Ngatno (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
Samsung Electronics is the largest electronics device manufacturer in the world. The increase of competition in the smartphone market and the decline in sales and market share of Samsung smartphones makes Samsung have to make a better marketing strategy. Nowadays, company require to be able to produce products with good quality and prices so consumers will feel satisfied and will increase their loyalty. This research used explanatory research with data collection methods using a questionnaire. The sample in this study is 100 respondents of Samsung smartphone users in Semarang with a purposive sampling become sample collection technique. The results showed that there was a positive and significant effect on product quality and price on customer satisfaction, product quality and price on customer loyalty, positive and significant effect on customer satisfaction on customer loyalty. Based on the sobel test results, there was an influence between product quality on customer loyalty through consumer satisfaction with partial mediation, and the effect of price on customer loyalty through customer satisfaction occurs full mediation. The suggestion in this research is that companies can reach all levels of the economy without reducing the quality of the products offered.